The Journey of the Old in the Novelette "Sebuah Mimpi Buat Hari Tua": A Gerontolgy Study - Hamid, Mohamed Nazreen Shahul; Yaapar, Md. Salleh (Malay Literature, 2018)
Shahnon Ahmad is a writer who has been elevated as a National Laurate by the Malaysian government. At the same time, he is a public intellectual well-liked by his community. As evidenced by the highly controversial novel Shit (1999), in producing his works he did not consider friends or opponents, and was never afraid in expressing his ideas and conviction. His works starting from the 60s often highlight various issues plaguing the communities in the urban and rural areas. However, since the early 2000s when Shahnon was at the later stage of his life, his writing had undergone an extreme change. He started to incorporate his experience of old age in his works. In this context, this article aims to analyse a novelette titled "Sebuah Mimpi Buat Hari Tua" (2003), with the focus on the human condition at old age. This work is analysed based on the conceptual framework of critical gerontology by Nancy R. Hooyman and H. Asuman Kiyak. This study finds that the novelette "Sebuah Mimpi Buat Hari Tua" fulfils three dimensions of gerontology, namely biological, psychological, and social. In fact, this literary work shows similarities between the author's perspectives and the views of scholars in critical gerontology. The findings of this study are important because they assert the position of "Sebuah Mimpi Buat Hari Tua" as a material for literary gerontology. Keywords: aging, critical gerentology, biological dimension, psychological dimension, social dimension, literary gerontolgy